2-2=4x+3x

Simple and best practice solution for 2-2=4x+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-2=4x+3x equation:


Simplifying
2 + -2 = 4x + 3x

Combine like terms: 2 + -2 = 0
0 = 4x + 3x

Combine like terms: 4x + 3x = 7x
0 = 7x

Solving
0 = 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
0 + -7x = 7x + -7x
Remove the zero:
-7x = 7x + -7x

Combine like terms: 7x + -7x = 0
-7x = 0

Divide each side by '-7'.
x = 0

Simplifying
x = 0

See similar equations:

| -2x+40=x+16 | | -x-2=2x+22 | | 7+1x=6 | | B=-6 | | 4x+10=120-9x | | -3x+44=x+20 | | 3x-9=x+1 | | 20=-4(5-m) | | 10.8x^8*.5x^2= | | 3x+12=102-6 | | 2+(4.5)= | | 6x+3-8x=-21 | | 5p+5t= | | 5(y+2)=3y-4+y | | (6-2x)(-5)= | | 4B-32B=36B-8BY | | 6x-2-x=13 | | 11x+19=5x+1 | | 116-4x=32x+24 | | 24x^2+17x+3=0 | | 2(3y-5x)= | | x^20= | | 4x-5=2x+8 | | -2+18d=19d+10 | | -6a(a+3)= | | 5n-2=-2n+1 | | 4r-8r+8+r= | | 36-6y=18x-6 | | x^2+10+23=0 | | -18+54X=27 | | 14x^2+17x-6= | | Y=[[x+5]] |

Equations solver categories